Two mice - Ruzzier, Sergio, 1966- (Clarion Books, Houghton Mifflin Harcourt, 2015)
Illustrations and minimal text follow two mice as they set off on an adventure that includes a shipwreck, kidnapping by a bird of prey, a narrow escape, and a moonlit stroll home.